Quantum Gravity: An Approach to Dynamics and Kinetic Energy of Photons - Patrinos, Konstantinos (New Trends in Physical Science Research Vol. 3, 2022)
Quantum gravitational theory, based on the hypothesis of the absolute reference system, reveals the function of the effects of the gravitational field at the microscopic and macroscopic scale. The quantum nature of gravitational potential, and the dynamics and kinetic energy of photons and elemen- tary particles under the influence of the gravitational field are studied, and a quantum interpretation of gravitational redshift is given. There is also a complete agreement of this quantum gravitational theory with the existing experimental data.